Adipositas & körperliche Aktivität - Kuni B; 2; Rühling NE; Wagner F; Hegar U; Roth C; Schmitt H; 4 (Deutsche Zeitschrift für Sportmedizin)
Background: Pediatric overweight is associated with higher incidences of musculoskeletal pain and injuries. It is still not known exactly what causes these problems. The purpose of this study was to compare overweight children with their non-overweight counterparts with respect to the leg axis and joint mobility.Methods: In all, 46 overweight children (girls: age: 8y. 9m. 1y. 2m., BMI-Percentile: 97.7 3.0; boys: age: 9y. 6m. 1y. 4m., BMI-Percentile: 98.2 2.5 (mean value standard deviation)) were compared with 42 non-overweight children (girls: age: 9 y. 3 mo. 1 y. 3 mo., BMI-Percentile: 26.9 20.8; boys: age: 9 y. 4 mo. 1 y. 2 mo., BMI-Percentile: 41.32 27.6). The passive range of joint motion in the lower extremity was assessed. Knee alignment was determined by digital photographs. Injury and pain history were recorded.Results: Overweight children showed deficits in the range of motion of the hip and the knee joints. Overweight girls had significantly higher knee valgus angles than non-overweight girls. In overweight children, ankle sprain (13/46) was the most common injury compared with six of 42 non-overweight children.Conclusions: Overweight children showed joint mobility restrictions and increased knee valgus angles when compared with non-overweight ones. These factors could influence the risk of sustaining injuries at the lower extremities. Prevention programs need to be established already in childhood.KEY WORDS: Paediatric Overweight, Paediatric Obesity, Leg Axis, Range of Motion, Injury